Supersolid-like sound modes in a driven quantum gas - Liebster, Nikolas; Sparn, Marius; Kath, Elinor; Duchene, Jelte; Strobel, Helmut; Oberthaler, Markus K. (Nature physics, 2025)
Driven systems are of fundamental scientific interest, as they can exhibit properties distinct from the same system at equilibrium. In certain cases, long-lived states of driven matter can emerge with new material properties. Here we probe the excitation spectrum of an emergent patterned state in a driven superfluid and find that its response is identical to that of a one-dimensional supersolid. By preparing wave packets as well as specific collective modes and probing their dynamics, we identify two distinct sound modes associated with spontaneously broken U(1) and translational symmetries. Consistent with the hydrodynamic description of superfluid smectics, longitudinal excitations propagate with finite velocities, whereas transverse perturbations exhibit diffusive behaviour. These results demonstrate how the conceptual framework of supersolidity can be used to characterize dynamic and far-from-equilibrium states.